Biological removal of pharmaceuticals from hospital wastewater in a pilot-scale staged moving bed biofilm reactor (MBBR) utilising nitrifying and denitrifying processes. (November 2018) - Ooi, Gordon T.H.; Tang, Kai; Chhetri, Ravi K.; Kaarsholm, Kamilla M.S.; Sundmark, Kim; Kragelund, Caroline; Litty, Klaus; Christensen, Alice; Lindholst, Sabine; Sund, Christina; Christensson, Magnus; Bester, Kai; et al.
Highlights: Pharmaceuticals from hospital wastewater are removed using pilot-scale MBBR. Removal above 20% was observed for each of 17 of the 22 compounds analyzed. 8 compounds had a near complete removal after 24 h of treatment. This includes iodinated X-ray contrast media, which used extensively in hospitals. Abstract: Hospital wastewater contains high concentrations of pharmaceuticals, which pose risks to receiving waters. In this study, a pilot plant consisting of six moving bed biofilm reactors (MBBRs) in series (with the intention to integrate Biological Oxygen Demand (BOD) removal, nitrification and denitrification as well as prepolishing Chemical Oxygen Demand (COD) for ozonation) was built to integrate pharmaceutical removal and intermittent feeding of the latter reactors aimed for micropollutant removal. Based on the experimental resultss, nitrifying MBBRs achieved higher removal as compared to denitrifying MBBRs except for azithromycin, clarithromycin, diatrizoic acid, propranolol and trimethoprim. In the batch experiments, nitrifying MBBRs showed the ability to remove most of the analysed pharmaceuticals, with degradation rate constants ranging from 5.0 × 10 −3 h −1 to 2.6 h −1 . In general, the highest degradation rate constants were observed in the nitrifying MBBRs while the latter MBBRs showed lower degradation rate constant. However, when the degradation rate constants were normalised to the respective biomass, the intermittently fed reactors presented the highest specific activity. Out of the 22 compounds studied, 17 compounds were removed with more than 20%.